QuEChERS applicability to measure land snail polycyclic aromatic hydrocarbons for risk assessment. Issue 5 (2nd July 2020) - Morin-Crini, Nadia; Louzon, Maxime; Amiot, Caroline; de Vaufleury, Annette
Abstract: The methods conventionally used for the extraction of organic pollutants in different environmental matrices are not suitable for measuring low concentrations of polycyclic aromatic hydrocarbons bioaccumulated in terrestrial snails that are both indicator of soil quality and a food item of various consumers including human being. A protocol, adapted from the QuEChERS method, originally designed for the extraction of pesticides in fruits and vegetables, in combination with gas chromatography-triple quadrupole mass spectrometry was developed to assess the bioavailability of polycyclic aromatic hydrocarbon extraction at low levels in soils to the soil quality bioindicator Cantareus aspersus . Bioaccumulation was measured in snails exposed ex situ for 28 days under controlled conditions to soils lightly or highly contaminated (sum of 16 molecules in the range 3.32–140 mg kg −1  dry weight). The method was validated (low limits of detection, linear calibration curves, good precision and trueness) and found to be efficient to show that strongly contaminated soils were not necessarily those that presented the highest bioavailable organics concentrations. This methodology offers a tool to assess the environmental risk of contaminated soils and to prioritize the management of polycyclic aromatic hydrocarbons-contaminated soils.